Recruiting, Retaining, and Retraining Secondary School Teachers and Principals in Sub-Saharan Africa - Mulkeen, Aidan; Chapman, David W.; DeJaeghere, Joan G.; Leu, Elizabeth (Washington, DC: World Bank, 2012)
This working paper is based on country case studies of Ethiopia, Ghana, Guinea, Madagascar, Tanzania, and Uganda, and an extensive literature review. In many parts of Africa, the demand for secondary teachers substantially exceeds the supply, due to factors such as secondary teacher attrition, bottlenecks in the teacher preparation system, and perceived unattractive conditions of service. Few countries have strong policies, strategies, and programs for recruiting able secondary school graduates to secondary teaching. The paper suggests several critical and promising areas for improvement in the quality of secondary teachers through new approaches to recruitment; pre-service and in-service teacher development; and improvements in the deployment, utilization, compensation, and conditions of service for teachers.